Visual Scanning Behavior and Attention Strategies for Shooting Among Expert Versus Collegiate Korean Archers. Issue 3 (June 2019) - Kim, Youngsook; Chang, Taiseok; Park, Inchon
This study analyzed differences in visual scanning behavior and resistance to distractions between Olympic and collegiate archers. The experiment required the participants to watch a test film comprising six stages corresponding to the phases of an archery performance. The recording emulated the archer's point of view. During initial phases of shooting, Olympic archers demonstrated more frequent and longer fixations than did their collegiate counterparts, whereas during the later phases of shooting, the groups' visual scanning patterns did not differ significantly. In a second experiment within this study, auditory and visual distractors led Olympic archers to exhibit fewer fixations of longer duration and less eye movement, regardless of the type of distraction. Thus, in each experiment, Korean national-team archers modified their attentional strategies more efficiently than collegiate archers, expanding and narrowing their focused attention based on task demands. These findings provide fundamental information on the nature of expert shooters' visual scanning patterns and have implications for developing training protocols for aspiring athletes.